Legal Protection of Teaching Staff in Light of The Maqasid Al-Shari’ah as outlined in Law Number 14 of 2005 Concerning Teachers And Lecturers - Fathul Ulum (STAI Syaichona Moh. Cholil Bangkalan, 2023)
This study examines the legal protection of teaching staff in light of the maqasid al-Shari’ah (objectives of Islamic law) as outlined in Law Number 14 of 2005 concerning Teachers and Lecturers. This research approach implements a qualitative approach with a normative juridical design. Data were obtained through primary sources, including laws on education and books on maqasid al-Shari’ah. The data collection technique of a literature study is a systematic process of gathering information from written sources. The results show that Law Number 14 of 2005, Articles 39 and 41, emphasize the obligation of the government, regional governments, communities, professional organizations, and educational institutions to protect teachers from violence, intimidation, threats, or unfair treatment. The purpose of Sharia lies in the principle of Hifz al-Nafs, which includes guaranteeing physical and psychological safety from acts of violence, abuse, or criminalization while carrying out teaching duties. This aligns with the human rights principles recognized in Islam to honor teachers. Keywords: legal protection, educators, maqasid al-Shari’ah, law